Allocating the real power transfer in deregulated power systems using genetic algorithm - Mohd Wazir, Mustafa, Dr.; Mohd Herwan, Sulaiman (Universiti Teknologi Mara (UITM), 2011)
3rd International Power Engineering and Optimization Conference (PEOCO 2009) organize by Universiti Teknologi Mara (UiTM), 3rd - 4th June 2009 at Shah Alam, Selangor, Malaysia.